Motivations to Leave Engineering: Through a Lens of Social Responsibility. Issue 3 (2nd September 2017) - Rulifson, Greg; Bielefeldt, Angela
ABSTRACT: Engineering should include concern for people, communities, and societal welfare at the heart of the profession. Focusing on these helping attributes of engineering may help draw individuals, particularly women, into the field. However, are prosocially motivated individuals leaving engineering during college due to the lack of social responsibility (SR) typically portrayed in their education? Understanding more about students' reasons for leaving in relation to perceived social responsibilities through their careers can help fill this literature gap. Thirty-four students initially majoring in engineering participated in a qualitative study of SR in engineering. Among this cohort, 7 of 14 women motivated to help people/society through engineering left, compared with 0 of 7 whose professional motivations were less related to social impact goals. Three rounds of hour-long interviews with nine students who left engineering explored reasons for leaving, if/how their personal SR impacted their decision, and social impact opportunities they envisioned through their new potential career path. The interviews show professional prosocial desires are motivation to leave combined with unsupportive environments, decontextualized technical courses, and curricular difficulty. These results provide insights for those trying to: understand why talented students choose to leave engineering, and create a more responsible and caring engineering profession.